BUSINESS PROCESS MANAGEMENT BASED ON QUALITY MANAGEMENT SYSTEM - Meng Zhizhong; Doszhan Raigul (Foundations and Trends in Research, 2025)
The article explores the theoretical and practical aspects of business process management, with a focus on quality management systems (QMS). The relevance of this topic is due to the need for organizations to enhance their operational efficiency and competitiveness in the era of digital transformation. The objective of this study is to examine approaches to integrating QMS into business processes and identify factors that contribute to their sustainable improvement. In this work, we employ methods such as content analysis, comparative analysis, and case studies. Through an examination of international case studies from companies like Siemens and Samsung, as well as a review of Kazakhstani enterprises, we demonstrate that successful QMS implementation requires a systematic approach, active management involvement, and a commitment to continuous improvement. Our analysis reveals variations in the level of QMS maturity across different countries and corporate cultures. The analysis leads to the realization that it is essential to tailor quality standards to the specific context of the organization and to seamlessly integrate the QMS into the organization’s strategic framework in order to foster sustainable progress and foster innovation